Copper/Zinc-Superoxide Dismutase in Human Epidermis: An Immunochemical Study - Altobelli, Giovanna G.; Van Noorden, Susan; Cimini, Vincenzo (Frontiers in Medicine, 2019)
The localization of copper and zinc-superoxide dismutase in normal and neoplastic human skin was examined with immunochemical techniques. Skin samples were taken from males and females of different ages, UV exposed and non-exposed areas and basal-/spino-cellular carcinomas. The enzyme was localized diffusely in the cytoplasm and was also found in the nuclei of epidermal cells, endothelial cells and other dermis cell types. The dismutase content in the epidermis was higher in males than females, UV-exposed than non-exposed and young than old people. In the tumors, the enzyme content of the superficial epidermal layers was higher than in the deep tumoral epithelial cells. These data suggest that the localization of Cu, Zn-SOD in skin tissues reflects the gender and age of the subject, the cell types and their normal or diseased state. Further studies based on the investigation of systemic changes of this enzyme in physiological and pathological epidermis could provide additional information on tumor cell generation.